Dynamics of the evolution of the strategy concept 1962–2008: a co‐word analysis - Ronda‐Pupo, Guillermo Armando; Guerras‐Martin, Luis Ángel (Strategic Management Journal, 2012)
Abstract The aim of this paper is to extend recent reflection on the evolution of strategic management by analyzing the field's object of study: strategy. We show how the concept of strategy has formed the backbone of the development of strategic management as an academic field and how consensus regarding it has evolved in the academic community during the stages of its historical development. We also address changes in the structure of the definition as it evolved through the growth of internal consistency, the centrality degree of the key terms that have shaped it, and how this evolution fostered the emergence of new research topics during the development of the discipline. Copyright © 2011 John Wiley & Sons, Ltd.